Synthesis and thermal conductivity characteristic of hybrid nanofluids – A review. (August 2017) - Leong, K.Y.; Ku Ahmad, K.Z.; Ong, Hwai Chyuan; Ghazali, M.J.; Baharum, Azizah
Abstract: Most of the researches on nanofluids conducted since the past decade focused on the single type particle based nanofluids. The characteristics of this type of nanofluid are well defined and explored. The advancement in nanomaterial has enabled the production of hybrid nanoparticles (nanocomposites) and recently, there are noticeable amount of researchers investigated on the characteristic of hybrid nanofluids. Therefore, the purpose of this review is to explore the synthesis method used by the researchers to develop hybrid nanofluids. Apart from that, hybrid nanofluid's thermal conductivity, challenges and future direction of this field are discussed. Based on the review, it is found that carbon nanotube is often combined with other material to synthesize hybrid nanoparticles. Hybrid nanofluids exhibit improved thermal conductivity characteristic. However, challenges such as hybrid nanofluids stability, selection of proper hybrid nanoparticles and its complex fabrication process and limited thermal conductivity model for hybrid nanofluids need to be addressed first. Better knowledge and understanding on these area are required in order to develop hybrid nanofluid which is not only provide enhanced thermal conductivity but also stable and does not require complicated synthesis process.